Embedded systems with arm cortex-m microcontrollers in assembly language and C - Zhu, Yifeng (E-Man Press LLC, 2017)
The book introduces basic programming of ARM Cortex-M cores in assembly and C at the register level, and the fundamentals of embedded system design. It presents basic concepts such as data representations (integer, fixed-point, floating-point), assembly instructions, stack, and implementing basic controls and functions of C language at the assembly level. It covers advanced topics such as interrupts, mixing C and assembly, direct memory access (DMA), system timers (SysTick), multi-tasking, SIMD instructions for digital signal processing (DSP), and instruction encoding/decoding.